2023
DOI: 10.3390/math11153290
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Gas-Solid Two-Phase Flows: Problems, Achievements and Perspectives (A Review)

Abstract: Mathematical modeling is the most important tool for constructing theories of different kinds of two-phase flows. This review is devoted to the analysis of the introduction of mathematical modeling to two-phase flows, where solid particles mainly serve as the dispersed phase. The main problems and features of the study of gas-solid two-phase flows are included. The main characteristics of gas flows with solid particles are discussed, and the classification of two-phase flows is developed based on these charact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…The size of particles with nanometer range and their high resistance to agglomeration and sedimentation allowed to gain very stable aqueous suspensions of nanoparticles without the application of any surface-active stabilizing agents. It is necessary to note, that a range of technical solutions for similar kinds of discharges was recently proposed by Kusenov and Ryzhkov with coworkers [7][8][9][10][11][12][13][14][15][16]. In these studies, discharges of various configurations, also taking into account electric and magnetic fields, as well as different mechanisms of influence on the objects, were applied in plasma experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The size of particles with nanometer range and their high resistance to agglomeration and sedimentation allowed to gain very stable aqueous suspensions of nanoparticles without the application of any surface-active stabilizing agents. It is necessary to note, that a range of technical solutions for similar kinds of discharges was recently proposed by Kusenov and Ryzhkov with coworkers [7][8][9][10][11][12][13][14][15][16]. In these studies, discharges of various configurations, also taking into account electric and magnetic fields, as well as different mechanisms of influence on the objects, were applied in plasma experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The downdraft mechanism and in-and-up mechanism are needed to start the process In conclusion, we mention works [119,146,147] in which the authors tried to take into account the influence of both mechanisms (downdraft mechanism and in-and-up mechanism) on tornado generation and dynamics in their calculations.…”
Section: Main Factors Of Tornadogenesismentioning
confidence: 99%
“…The results showed that the particles had a small diameter and showed hysteresis effects in the reaction zone. Varaksin et al [13] performed multiphase flow simulations with differently sized particles (polydisperse particles) and concluded that differently sized particles produce different velocities, affect the gas flow differently, and tend to collide with each other at lower concentrations. Yue et al [14] used the CFD-DEM method to study the effect of the particle density on nozzle deflection under three conditions of constant fluidization velocity, amplified fluidization velocity, and particle density.…”
Section: Introductionmentioning
confidence: 99%